2012
DOI: 10.3390/ijms13066651
|View full text |Cite
|
Sign up to set email alerts
|

Proximate Composition and Antioxidant Potential of Leaves from Three Varieties of Mulberry (Morus sp.): A Comparative Study

Abstract: In this study, leaves of three indigenous varieties of Mulberry namely, Morus alba L., Morus nigra L. and Morus rubra L. were investigated for their antioxidant potential and their proximate composition was determined. The yields of 80% methanolic extracts ranged between 8.28–13.89%. The contents of total phenolics (TPC), total flavonoids (TFC) and ascorbic acid (AA) ranged between 16.21–24.37 mg gallic acid equivalent (GAE)/g, 26.41–31.28 mg rutin equivalent (RE)/g and 0.97–1.49 mg/g, respectively. The antiox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
111
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(132 citation statements)
references
References 48 publications
15
111
5
1
Order By: Relevance
“…In addition, it has been shown that mulberry leaves contained various phytochemicals such as flavonoids, polyphenols, carotenoids etc. (Iqbal et al, 2012). Various studies have shown that natural phytochemicals in mulberry leaves could have various health improvement effects such as hypoglycemic (Mudra et al, 2007), hypolipidemic (Aramwit et al, 2011), antihypertensive effects (Yang et al, 2012), and…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been shown that mulberry leaves contained various phytochemicals such as flavonoids, polyphenols, carotenoids etc. (Iqbal et al, 2012). Various studies have shown that natural phytochemicals in mulberry leaves could have various health improvement effects such as hypoglycemic (Mudra et al, 2007), hypolipidemic (Aramwit et al, 2011), antihypertensive effects (Yang et al, 2012), and…”
Section: Discussionmentioning
confidence: 99%
“…Total flavonoids and phenolics showed a linear relationship with antioxidant capacity (CUPRAC: R2 = 0.9070 and R2 = 0.8959, respectively), indicating that flavonoids and phenolics were the major contributors to the antioxidant capacity. Shahid et al, (2012) observed radical cation scavenging capacity and ferric ion reducing power and values ranged between 1.89-2.12, 6.12-9.89 and 0.56-0.97 mMTrolox equivalent/g of dried leaves, respectively. The antioxidant activity of leaf extracts was evaluated by measuring 1,1-diphenyl-2-picrylhydrazyl (DPPH•) radical scavenging activity, 2,2'-azino-bis-(3-ethylbenzthiazoline-6-sulphonic acid (ABTS•+) radical cation scavenging capacity and ferric ion reducing power and values ranged between 1.89-2.12, 6.12-9.89 and 0.56-0.97 mMTrolox equivalent/g of dried leaves, respectively.…”
Section: Phytochemical Compositionmentioning
confidence: 99%
“…The contents of total phenolics (TPC), total flavonoids (TFC) and ascorbic acid (AA) ranged between 16.21-24.37 mg gallic acid equivalent (GAE)/g, 26.41-31.28 mg rutin equivalent (RE)/g and 0.97-1.49 mg/g, respectively. The antioxidant activity values ranged between 1.89-2.12, 6.12-9.89 and 0.56-0.97 mMTrolox equivalent/g of dried leaves, respectively (Shahid et al, 2012).In general, fresh mulberry showed higher contents of total phenolics (0.49-57 fold higher), flavonoids (0.02-162 fold higher), anthocyanins (6-12 fold higher) and antioxidant capacity (0.72-691 fold higher) compared to other products. Total flavonoids and phenolics showed a linear relationship with antioxidant capacity (CUPRAC: R2 = 0.9070 and R2 = 0.8959, respectively), indicating that flavonoids and phenolics were the major contributors to the antioxidant capacity (Senem et al, 2013).…”
Section: Phytochemical Compositionmentioning
confidence: 99%
“…5 The major constituents of plant leaves include Chalcomoracin, Morachalcone A-C and flavanoids such as Luteolin, Rutin and Chlorogenic acid. [6][7][8] Hence, the present study is aimed at screening of extracts prepared using solvents with increasing polarity from theMorus alba leaves for their potential to inhibit free radicals (anti-oxidant activity) as well as to protect the DNA from free radical induced breaks (anti-clastogenic activity).…”
Section: Introductionmentioning
confidence: 99%